Carbon Fiber/Epoxy Composite Ring-disk Electrode: Fabrication, Characterization and Application to Electrochemical Detection in Capillary High Performance Liquid Chromatography - Xu, Xiaomi (2009)
Carbon fiber/epoxy composite materials, which are manufactured using the pultrusion process, are commercially available in various shapes and sizes at very low cost. Here we demonstrate the application of such a material as an electrochemical detector in a flow system. Cyclic voltammetry shows that the material's electrochemical behavior resembles that of glassy carbon. Using tube and rod composites, we successfully fabricated a ring-disk electrode with a 20 μm gap between the ring and the disk. The narrow gap is favorable for mass transfer in the generator-collector experiment. This composite ring-disk electrode is assembled in a thin-layer radial-flow cell and used as an electrochemical detector. The disk electrode, placed directly opposite to the flow inlet, is operated as a generator electrode with the ring electrode being a collector. The high collection efficiency on the ring electrode (0.8 for a chemically reversible species) enhances the detection selectivity.